Relasi Kuasa dan Perjuangan Kesetaraan Gender: Narasi Perempuan Mengelola Pertambangan Minyak Artisanal di Sumatera Selatan - Sununianti, Vieronica Varbi (RESIPROKAL: Jurnal Riset Sosiologi Progresif Aktual, 2024)
This article emphasizes power relations and gender equality dynamics in resource management in the artisanal oil mining sector of South Sumatra. Michel Foucault’s perspective on knowledge and power is used to explore how power structures that change women’s roles emerge as a result of livelihood shifts from rubber farming to artisanal oil mining. The descriptive qualitative study with live-in assisted in the process of interviewing and observing a number of artisanal oil miners as well as women in Dusun Tue, Musi Banyuasin Regency, South Sumatra. Historically, women were active and equal in economic activities based on rubber farming. However, the emergence of artisanal mining has seen women’s roles gradually excluded from productive spaces, especially at mining sites due to perceived “taboos”. This exclusion is part of a power strategy that produces gender inequality through normalized social norms. Nevertheless, a critical analysis perspective helps to see the uniqueness of various forms of power and resistance and women’s agents to resist such discrimination. Even though they are excluded from mining sites, women remain involved in mining activities through mining partnerships, scavenging for oil spills, and even determining well-drilling locations through the ritual of “meniduri tanah”. Women also play an important role in local economic empowerment through micro, small, and medium enterprises, thus continuing to contribute to family and community livelihoods. This study illustrates that power is contested in various contexts. In artisanal oil mining, the relationship between men and women reveals not only structural inequality but also the process of women’s struggle over their role in the local economy. Hence, this study provides an important perspective on the role of gender in resource management in the informal sector. Further, economic changes not only increase gender inequality but also enable empowerment and resistance strategies.